2019
DOI: 10.3390/ijms21010198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osseointegration Capability of Poly(ether ether ketone) via Combined Phosphate and Calcium Surface-Functionalization

Abstract: Biomedical applications of poly(ether ether ketone) (PEEK) are hindered by its inherent bioinertness and lack of osseointegration capability. In the present study, to enhance osteogenic activity and, hence, the osseointegration capability of PEEK, we proposed a strategy of combined phosphate and calcium surface-functionalization, in which ozone-gas treatment and wet chemistry were used for introduction of hydroxyl groups and modification of phosphate and/or calcium, respectively. Surface functionalization sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The authors in these cases demonstrated how the growth factor could influence and improve cell adhesion, osteogenic and angiogenic events, and osseointegration process. Sunarso et al [70] evaluated the osteogenic anchorage, and osteointegration of titanium-made dental implants. Several modifications on the implant surfaces such as sandblasting, anodizing, acid attack, and calcium phosphate coverage have been designed in an attempt to improve the performance of the dental implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in these cases demonstrated how the growth factor could influence and improve cell adhesion, osteogenic and angiogenic events, and osseointegration process. Sunarso et al [70] evaluated the osteogenic anchorage, and osteointegration of titanium-made dental implants. Several modifications on the implant surfaces such as sandblasting, anodizing, acid attack, and calcium phosphate coverage have been designed in an attempt to improve the performance of the dental implant.…”
Section: Discussionmentioning
confidence: 99%
“…The authors in these cases demonstrated how the growth factor could influence and improve cell adhesion, osteogenic and angiogenic events, and osseointegration process. Sunarso et al [ 70 ] evaluated the osteogenic capability of polyether-ether-ketone (PEEK). This study demonstrated that immobilization of phosphate or calcium increased the osteogenesis of rat mesenchymal stem cells compared with bare PEEK, including cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when compared to titanium, PEEK implants had minimal osteoblast differentiation [ 70 ], and they did not display any osteoconductive properties [ 49 , 71 ]. However, favorable bony deposit could be found in the titanium-coated PEEK (Ti-PEEK), as shown by Cheng et al [ 72 ].…”
Section: Peek Materials In Oral Implantologymentioning
confidence: 99%
“…CaP coatings have been shown to remarkably enhance the proliferation of MC3T3-E1 cells and apatite-forming ability in simulated body fluid (SBF) (Jabbari et al, 2018 ). In another study, surface functionalization with a combination of phosphate and calcium remarkably promoted the osteogenic activity of rabbit bone marrow-derived mesenchymal stem cells in vitro and the osseointegration ability in vivo (Sunarso et al, 2019 ). It is worth noting that amorphous calcium phosphate can be fabricated on the PEEK surface within 1 day, and strong adhesion with PEEK can be obtained using a novel PrA treatment (involving three steps: H 2 SO 4 treatment, O 2 plasma treatment, and alkaline SBF treatment) (Yabutsuka et al, 2017 , 2018 ).…”
Section: Modifications Inspired By the Components Of Bonementioning
confidence: 99%